“Evaluación de los productos obtenidos en la curticion de pieles con corteza de ucshaquiro colorado (sclerolobuim paniculatum)” - Ascón Dionico,Gregorio Mayer (1997)
This paper discusses obtaining sole and leather from skin fresh beef as raw and subjected to different treatments with colorado Ucshaquiro bark (Sclerolobium paniculatum) as tanning, using concentrations of 5, 10 and 20 Kg of crust per each 20 liters of water for each treatment. To the end the trials is submitted to evaluation each an of them samples obtained, and for the interpretation of such results is used the method statistical of DBCR. The sample treated 869 to a pH of 6.0, temperature of 37 ° C and a concentration of 5 kg of bark/20 liter ~ water, in a time of 20 days tanning, has the best characteristics in terms of flexibility and strength for sole, and corresponds to T2; and sample 503, treated at a pH of 3.0, temperature of 32 ° C, at a concentration of 5 Kg of bark/20 litres of water, in a time of 18 days tanning, possesses the best characteristics in terms of color, res...